The role of a reference yield fitting technique in the fund transfer pricing mechanism - Dziwok, Ewa (Znaczenie techniki modelowania w mechanizmie cen transferowych, 2019)
The funds transfer pricing (FTP) structure has become the basis for the process of asset and liability management (ALM) in a modern bank. According to the supervisory documents, FTP is thus a regulatory constraint and an important tool in the ALM process. What is more, institutions should have an adequate internal transfer pricing mechanism based on the reference rate delivered from the market in the form of the yield curve. The fragility and sensitivity of the reference yield over time could have huge consequences for the liquidity risk management process. The aim of the article is to compare the methods of estimation FTP reference yield depending on the goodness-of-fit methodology (least square methods based on short rates (up to 1 year) and prices taken from the Polish market will be considered)). The data taken into account cover the period between 2005-2017 and the results obtained allow to point out the periods when disturbances on the market affected the goodness of a model’s fit to real data and, consequently, have an effect on the fund transfer pricing mechanism
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 2, s. 16-24
Keywords: liquidity risk; risk management; fund transfer pricing; pomiar ryzyka; ryzyko płynności; ceny transferowe